Growth, biomass and lipid productivity of a newly isolated tropical marine diatom, Skeletonema sp. UHO29, under different light intensities - Indrayani Indrayani; Haslianti Haslianti; Asmariani Asmariani; Wellem Muskita; Abdul Muis Balubi (Biodiversitas Journal of Biological Diversity, 2020)
Abstract. Indrayani I, Haslianti H, Asmariani A, Muskita WH, Balubi M. 2020. Growth, biomass and lipid productivity of a newly isolated tropical marine diatom, Skeletonema sp. UHO29, under different light intensities. Biodiversitas 21: 1498-1503. Light is one of the important factors affecting growth and biochemical composition of microalgae. The aim of this study was to determine growth, biomass and lipid productivity of a newly isolated marine diatom, Skeletonema sp.UHO29 under different light intensities. The Skeletonema sp. was cultured in 300 mL conical flasks containing 150 mL of f/2 medium under three different light intensities (28, 60 and 110 ?mol photons m-2 s-1 ) with three replications. The cultures were incubated under ambient room temperatures, and a cycle of 12 hours light and 12 hours dark, in batch modes for two weeks. The results showed that the highest specific growth rate (0.56 d-1) was achieved at the highest light intensity (110 ?mol photons m-2 s-1) and the lowest (0.11 d-1) was obtained at the lowest light intensity (28 ?mol photons m-2 s-1). The highest biomass yield (0.62 g L-1) and biomass productivity (0.34 g L-1 d-1) was achieved at the highest light intensity. However, the highest lipid yield (0.175 g L-1), lipid content (28.78% ash-free dry weight) and lipid productivity (0.067 g L-1 d-1) were achieved at medium light intensity. The alga prefers high light intensity for higher growth rate and biomass productivity but it produces more lipids at medium light intensity. This study indicated that the Skeletonema sp.UHO29 is a potential species for outdoor mass cultivation and is a promising microalgal strain for use as a biodiesel feedstock due to its high growth rate, high biomass and lipid productivity.